TOPSIS Fuzzy Application Program Fase II - Martinez, Rodrigo J. (2011)
While there are many models of multi-criteria decision making based on fuzzy logic, the software available for solving problems of this kind is scarce. Therefore, the objective of this paper is to present the continuation of the software proposed in the paper “Topsis Fuzzy Aplication Program”, presented at the XXIV ENDIO – XXII EPIO in 2011 [1] which allows to solve decision problems with TOPSIS fuzzy method using linguistic labels, proposed by Chen (2000), including critical enhancements to the system arising as a result of its extensive use.